The Influence Green Accounting, Environmental Performance, and Company Size on Financial Performance with CSR Moderation in Indonesian Stock-Listed Mining Companies - Yolanda Agustina Ananta; Azhar Maksum; Erlina Erlina (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the influence of green accounting, environmental performance, and firm size on financial performance, with Corporate Social Responsibility (CSR) as a moderating variable. The research focuses on mining sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2024 period. The study employs a quantitative approach using secondary data obtained from annual reports, sustainability reports, and financial statements. The research sample was determined using a purposive sampling method, resulting in 17 companies with a total of 102 observations. Data analysis was conducted using panel data regression. The findings indicate that green accounting has a positive effect on financial performance, environmental performance has a positive effect on financial performance, and firm size also positively influences financial performance. However, Corporate Social Responsibility (CSR) does not moderate the influence of green accounting on financial performance. CSR also does not moderate the relationship between environmental performance and financial performance. Conversely, CSR is found to moderate the effect of firm size on financial performance.